Optimal land use allocation for the Heathrow opportunity area using multi-objective linear programming - Oléron-Evans, Thomas P.; Salhab, Melda (Land use policy, 2021)
The London Plan, the Greater London Authority’s spatial development strategy for London, has defined Heathrow as an Opportunity Area – an area with the capacity to support additional homes and jobs – since 2004, but progress on developing the area has been minimal. Uncertainty around the expansion of Heathrow Airport appears to have adversely affected progress. Nevertheless, the most recent London Plan stipulates that the Heathrow Opportunity Area should accommodate 13,000 new homes and 11,000 new jobs. In this article, multi-objective linear programming is used to investigate whether these figures are achievable given constraints on land availability and land use mix. How land uses might best be assigned to maximise home, job and gross value added (GVA) creation within the Heathrow Opportunity Area is also explored. The main contributions are to provide independent scrutiny of London’s development strategy and to present a mathematical framework for land use allocation planning decisions in urban areas. Findings show that given 700 ha of available land, as indicated in the London Plan, home and job creation figures can be met. However, there is insufficient brownfield land to meet these targets, and development on Green Belt land would very likely be necessary. Strong land use allocations for the area are found to more heavily feature financial and professional services, other office-based businesses, and shops. Rather than presenting a single land use “solution”, results are presented using a wide range of visualisations to illustrate key trade-offs between different goals, with the secondary aim of promoting multi-objective linear programming to planners as a valuable tool to support spatial decisions and policy making. •Study aims to optimise land use allocation using multi-objective linear programming.•Detailed research is presented into history and context of the Heathrow Opportunity Area.•Two methods provide a range of allocations, maintaining flexibility for planners.•Heathrow Opportunity Area targets for home and job creation found to be achievable.•Brownfield land is insufficient; targets likely require development on Green Belt.